2006
DOI: 10.1021/es060691k
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interactions between DMSA-Coated Maghemite Nanoparticles and Human Fibroblasts:  A Physicochemical and Cyto-Genotoxical Study

Abstract: Although the current production of oxide nanoparticles may be modest, the wide range of proposed applications and forecasted growth in production has raised questions about the potential impact of these nanoparticles on the environment and human health. Iron oxide nanoparticles have been proposed for an increasing number of biomedical applications although in vitro toxicity depending on the particles coating has been evidenced. The aim of this study was to examine the potential in vitro cyto- and genotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(128 citation statements)
references
References 32 publications
7
117
0
4
Order By: Relevance
“…If, however, the surface of the particles is totally covered, the dispersion may be stabilized, which will reduce the aggregation induced by both electrochemical and steric interactions [34]. Electrostatic modifications of colloidal stability can also occur after chemisorption of small inorganic or organic molecules [35]. Furthermore, the particle may adsorb contaminants or small biological entities and act as a vector for their transport in the environment [36][37][38][39][40].…”
Section: Nanoparticle Releasementioning
confidence: 99%
“…If, however, the surface of the particles is totally covered, the dispersion may be stabilized, which will reduce the aggregation induced by both electrochemical and steric interactions [34]. Electrostatic modifications of colloidal stability can also occur after chemisorption of small inorganic or organic molecules [35]. Furthermore, the particle may adsorb contaminants or small biological entities and act as a vector for their transport in the environment [36][37][38][39][40].…”
Section: Nanoparticle Releasementioning
confidence: 99%
“…Several previous studies examined the effects of DMSA-MNP on different cell types, and showed little reduction in cell viability [11,16,40]. These studies used low MNP doses, however, or incubation times too short to permit analysis of all possible toxic effects of iron oxide nanoparticles.…”
Section: In Vitro Dmsa-mnp Cytotoxicitymentioning
confidence: 99%
“…Previous studies analyzed in vitro toxicity of several kinds of iron oxide MNP on different cell types, with variable results. Whereas some showed that MNP can reduce cell viability, affect cell morphology or adhesion, or impair cell metabolism [6,[11][12][13], others found no significant cytotoxic effects [14][15][16]. These contradictory results are closely related to a concept known as "cell vision", refering to the contact point between nanoparticles and cells.…”
Section: Introductionmentioning
confidence: 99%
“…412 We summarize the characterization of nanoparticles and the cell models used in all of these studies in Table 5. The genotoxic potential of other nanoparticles, such as QD, 414 nanodiamonds, 413 aluminum oxide, 172 cobalt, 400 cobalt chrome alloy, 415 and maghemite nanoparticles, 416 have also been investigated. However, comparison of these results is difficult because of the great differences in the experimental protocols used.…”
mentioning
confidence: 99%